KONTROVERSI PENERAPAN HUKUM CAMBUK DI ACEH DALAM TRADISI SYARIAH DAN PRINSIP HAK ASASI MANUSIA - Asyisyifa, Ananda Fia; Sumanto, Listyowati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: This study aims to analyze the implementation of caning law in Aceh within the framework of sharia law and how the law interacts with human rights principles. This study also explores the regulation of caning law in the Indonesian legal system and identifies potential conflicts between Aceh's local authority in implementing sharia and Indonesia's obligation to comply with international human rights standards. With the type of normative legal research, this study is expected to provide a deeper understanding of the balance between the implementation of sharia law and the protection of individual rights. Qualitative secondary data analysis. Drawing conclusions using deductive logic. The results of the study indicate that the implementation of caning law in Aceh, although based on sharia law regulated through Qanun Jinayat and given legitimacy within the framework of regional autonomy, still causes controversy related to violations of human rights principles.Keywords: Controversy, Caning Law, Human Rights